Differences in the compatibility of infection between the liver flukes Fascioloides magna and Fasciola hepatica in a Colombian population of the snail Galba sp - Dreyfuss, G; Correa, A C; Djuikwo-Teukeng, F F; Novobilský, A; Höglund, J; Pankrác, J; Kašný, M; Vignoles, P; Hurtrez-Boussès, S; Pointier, J P; Rondelaud, D (Journal of helminthology, 2015)
Experimental infections of Galba sp. (origin, Colombia) with allopatric isolates of Fasciola hepatica from France or Fascioloides magna from the Czech Republic were carried out during five successive snail generations to determine if this lymnaeid might sustain complete larval development of either parasite. In snails exposed to F. hepatica, 7 of 400 snails harboured several rediae and only two snails contained a small number of free cercariae on day 50 post-exposure. In contrast, the intensity of F. magna infection in Galba sp. progressively increased from the F1 to F5 generations. Spontaneous cercarial shedding of F. magna occurred in 7 of 100 Galba sp. belonging to the F5 generation and the number of shed cercariae did not differ significantly from that noted in control Galba truncatula of French origin. Galba sp. from Colombia can be added to the list of potential intermediate hosts for F. magna.
Keywords: Animals; France; Česká republika; Fasciolidae; Fasciola hepatica; Fascioliasis; zvířata; mužské pohlaví; Female; Male; Snails; fasciolóza; Francie; Czech Republic; Disease Reservoirs; hlemýždi; zdroje nemoci; ženské pohlaví